Pesantren-Based School Culture Development: The Practice Of 'Kitab Kuning' Learning In School - Edi Nurhidin (At-Tarbiyat, 2022)
This paper aims to show the practice of kitab kuning learning in elementary schools as the basis for developing school culture. There are two main questions in this research. First, how is the process of kitab kuning learning? Second, how is the sustainability of the kitab kuning learning program? The research method used qualitative with a single case study design at the Nahdlatul Ulama Islamic Elementary School (SDI NU) Pare, Kediri Regency. This study found that kitab kuning learning as a special activity followed the pattern of learning the kitab kuning in pesantren (Islamic boarding schools) with the two main learning methods, Arabic pegon learning and bandongan. Second, the learning of kitab kuning starting in the 2022/2023 school year is not only a special program but has continued as part of the school curriculum by integrating it with the curriculum so that all students learn it. The integration form combined Pesantren-style learning with Arabic subjects. These two findings indicate the school's consistency in preserving the pesantren tradition as the primary basis for developing a school culture.